Número de olhos cegos por glaucoma detectados em primeira consulta num hospital universitário - Rodrigues, Antonio Carlos [UNESP]; Silva, Maria Rosa Bet De Moraes [UNESP]; Schellini, Silvana Artioli [UNESP] (Conselho Brasileiro de Oftalmologia, 1998)
The authors studied retrospectively 695 glaucoma pacients (1390 eyes) from the Hospital of the Faculty of Medicine of Botucatu - UNESP, attended from 1986 to 1996 to evaluate the number of blind eyes (VA < 0.1) at the first visit. This VA was correlated with elements of identification, ophthalmological parameters and glaucoma types. The authorsfound 502 eyes (36.12%) with VA < 0.1 at the first visit. This VA was correlated with: age > 60years in 41.79%) of the eyes, arterial hypertension in 36.43%o, negative family history for glaucoma in 37.18%, cup/disc ratio > O. 5 associated with other glaucomatous signs of the papilla in 52.45% and 1OP > 22 mmHg in 52.24%. The glaucoma types more frequently associated with VA < 0.1 at the first visit were: neovascular glaucoma (90.90%) glaucoma due to uveitis (75.00%) and pseudoexfoliation (60.00%).

Foram estudados retrospectivamente 695 pacientes (1390 olhos) portadores de glaucoma do H.C. da Faculdade de Medicina de Botucatu - UNESP, atendidos de 1986 a 1996, com o objetivo de avaliar o número de olhos cegos (AV < 0,1) na primeira consulta. Esta AV foi correlacionada aos dados de identificação, parâmetros oftalmológicos e tipos de glaucoma. Foram encontrados 502 olhos (36,12%) com AV < 0,1 no momento de chegada. Esta AV estava associada significativamente: à idade > 60 anos em 41,79% dos olhos, hipertensão arterial em 36,43%, ausência de históriafamiliar de glaucoma em 37,18%, escavação de papila > 0,5 associada a outros sinais glaucomatosos da papila em 52,45% e PIO > 22 mmHg em 52,24%, Quanto ao tipo de glaucoma os que deram entrada com maior porcentagem de olhos cegos foram o glaucoma neovascular (90,90%), glaucoma por uveíte (75,00%) e glaucoma com pseudo-exfoliação (60,00%).
Number of blind eyes due to glaucoma detected at the first visit at a university hospital
Keywords: Glaucoma; Blindness; University hospitals; Glaucoma; Cegueira; Hospitais Universitários